When Shareholders Are Creditors: Effects of the Simultaneous Holding of Equity and Debt by Non-commercial Banking Institutions - Jiang, Wei; Li, Kai; Shao, Pei (Review of Financial Studies, 2010)
[This article provides a comprehensive analysis of a new and increasingly important phenomenon: the simultaneous holding of both equity and debt claims of the same company by non-commercial banking institutions ("dual holders"). The presence of dual holders offers a unique opportunity to assess the existence and magnitude of shareholder-creditor conflicts. We find that syndicated loans with dual holder participation have loan yield spreads that are 18-32 bps lower than those without. The difference remains economically significant after controlling for the selection effect. Further investigation of dual holders' investment horizons and changes in borrowers' credit quality lends support to the hypothesis that incentive alignment between shareholders and creditors plays an important role in lowering loan yield spreads.]